Controlled dilatation of the uterine cervix – an experimental visceral pain model - Bajaj, Priti; Drewes, Asbjørn M; Gregersen, Hans; Petersen, Poul; Madsen, Hans; Arendt-Nielsen, Lars (Pain (Amsterdam), 2002)
Pain originating from the female reproductive organs is a substantial clinical problem to treat. Experimental models may be a tool for the study of visceral pain mechanisms and hence provide information to aid in formulating new treatment strategies. The aim was to develop and evaluate the performance and safety of a model for nociceptive stimulation of the uterine cervix by balloon dilatation using impedance planimetry. Three consecutive (repeated) dilatations at 1 ml/min, an isovolumetric and a fast dilatation at 2 ml/min were performed. Pilot studies were conducted in vitro on hysterectomy specimens, followed by application of the model in 14 healthy females. Subjects indicated the quality of perception and pain during dilatations by verbal reports and the McGill Pain Questionnaire (MPQ), and the intensity by a continuous electronic visual analog scale. The pain location was marked on an anatomical map. The balloon cross-sectional area (CSA) was measured simultaneously. The experimental procedure was atraumatic. Pain was evoked in all subjects, with referral to the hypogastric and low back regions. The word descriptors on the MPQ and the areas of referred sensations were similar to that seen clinically in abortion, labor and menstrual pain. The pain intensity correlated with balloon CSA ( r=0.9, P<0.001). No significant differences were found for the balloon volumes (4.2, 3.8 and 3.9 ml) or CSA (163, 122 and 123 mm 2) to pain threshold (PT) for repeated dilatations, suggesting the reliability of the model. There was significant correlation between the balloon volume and CSA to reach the PT for single and repeated cervical dilatations. During isovolumetric distension, greater overall pain intensity was demonstrated for the prolonged as compared to the shorter duration cervical stimulation. In conclusion, this is the first human experimental pain model for dilatation of the uterine cervix, providing a safe, controlled, quantifiable stimulus that evoked reliable pain scores. The model thus provides a new possibility to study gynecological pain and may lead to better characterization and treatment of female visceral pain syndromes.